2010
DOI: 10.1016/j.febslet.2010.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Swapping of the N‐terminus of VDAC1 with VDAC3 restores full activity of the channel and confers anti‐aging features to the cell

Abstract: a b s t r a c tVoltage-dependent anion-selective channels (VDACs) are pore-forming proteins allowing the permeability of the mitochondrial outer membrane. The VDAC3 isoform is the least abundant and least active in a complementation assay performed in a yeast strain devoid of porin-1. We swapped the VDAC3 N-terminal 20 amino acids with homologous sequences from the other isoforms. The substitution of the VDAC3 N-terminus with the VDAC1 N-terminus caused the chimaera to become more active than VDAC1. The VDAC2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 49 publications
4
76
0
Order By: Relevance
“…The carbon source was, respectively, glucose or glycerol and the incubation temperature 28°C or 37°C. As a control, BY4742, a wild type strain, Δpor1, a strain devoid of endogenous porin1 [3,28] growth in the absence or after transformation with hVDAC1 or hVDAC3. B) Serial dilution of yeast colony, showing their relative growth, in the presence of 60 mM acetic acid. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon source was, respectively, glucose or glycerol and the incubation temperature 28°C or 37°C. As a control, BY4742, a wild type strain, Δpor1, a strain devoid of endogenous porin1 [3,28] growth in the absence or after transformation with hVDAC1 or hVDAC3. B) Serial dilution of yeast colony, showing their relative growth, in the presence of 60 mM acetic acid. …”
Section: Resultsmentioning
confidence: 99%
“…Concerning the 3-D arrangement of VDAC3, in the absence of an experimental structure, it is possible to hypothesize that some domains of the protein can play a different role in VDAC3 with respect to VDAC1. In particular we have previously demonstrated that the swapping of the N-terminal domain of VDAC3 with the same domain from VDAC1 fully restores not only the ability to complement the growth defect in Δporin1 yeast but also confers electrophysiological properties largely overlapping those of VDAC1 to the chimera [28]. Either N1-VDAC3 purified from yeast transformed with a shuttle vector carrying the sequence of the chimera, or recombinant N1-VDAC3, extracted from E. coli and purified with Ni-NTA chromatography, are able to form large pore similar to those of VDAC1.…”
Section: Discussionmentioning
confidence: 99%
“…1B). It has been speculated that these cysteines may play some role in oxidative stress response and reactive oxygen species control, by acting as molecular buffers in mitochondria (4,8). Hence, despite the 72% sequence identity between hVDAC-1 and hVDAC-2, and the overall functional similarities (7), major behavioral differences exist between these isoforms.…”
mentioning
confidence: 97%
“…Furthermore, it plays a key role in regulating conductance of calcium, ATP, NADH, metabolites etc., voltage-dependent switch in ion conductance, and hexokinase binding (5-7). Owing to its major function, VDAC is now being referred to as the "governor of mitochondrial bioenergetics" (8). The wealth of structural and functional information on VDACs has primarily been obtained from the isoform 1 from human and murine sources (1, 2, 5, 6, 8 -12).…”
mentioning
confidence: 99%
See 1 more Smart Citation